The defects of the law - Carpio Marcos, Edgar (2015)
All legislative acts shall have continuity in time. However, sometimes these acts contain defects that cause their unconstitutionality and the subsequent expulsion from the legal order. The important  question that arises is: When can a legislative act be declared unconstitutional? Whichare the defects that cause the expulsion of a law from the legal system?In this article, the author seeks to address these questions through a presentation of the legal defects that cause the invalidity of an act. The author pays special attention to the discussed legislative power excess defect, contrasting foreign case law with jurisprudence from the Peruvian Constitutional Court to determine if it is enough for  an  act  to  have  this  defect to be declared unconstitutional.